Corak Perbelanjaan Kad Kredit Islam Oleh Pelanggan Bank - Mohd Diah, Md Saleh (2011)
The purpose of this study was to examine the expenditure pattern of the Islamic credit card. The objective of this study was to investigate the level of satisfaction of the Islamic credit card usage patterns, the different levels of customer satisfaction using the Islamic card based on demographic factors and study the factors of service quality dimensions of Islamic credit cards with customer satisfaction. The survey method was used to collect primary data. Some sample clients from private and government staff in UUM, Bukit Kayu Hitam, Unimap, Kangar and Kuala Perlis. Data were collected through questionnaires and analyzed using the Statistical Package for Social Sciences (SPSS). The results of this study showed a positive correlation between spending patterns of customer satisfaction. In conclusion, the research objective is to analyze the behavior and spending patterns of Islamic credit card are achieved.